What has Changed? Stance and Engagement in Mahathir Mohamad’s UNGA Speeches - Mengyu, He; Rahim, Hajar Abdul (Pusat Pengajian Ilmu Kemanusiaan, 2019)
The analysis of language in communication is not only the analysis of propositional information, but also the analysis of how speakers and writers express their ideas (Hyland, 2008). The speaker/writer-audience interaction becomes an important site for language analysts as this interaction reflects the speakers and writers’ purposes and provides a tool in understanding language use. As Hyland (2001a) proposes that the success of a dialogue with the audience depends largely on a balance between the language users’ claims and their assumptions of the audiences. Stance and engagement commonly addressing to the audiences explicitly are rhetorical ways to achieve this interaction. These rhetorical strategies allow language users to invoke the readers and to include them as participants by assuming their possible reactions and knowledge. Past studies on stance and engagement have mainly focused on written discourse (e.g., Crosthwaite, Cheung, & Jiang, 2017; Hyland, 2001b; Hyland & Jiang, 2016; Jiang & Ma, 2018). These studies suggest something of writers’ senses to imagine the potential audiences. Despite the current massive interest in stance and engagement, spoken discourse is a disregarded discourse which has largely escaped the notice of language analysts. This study thus addresses this research gap, offering an account of Mahathir Mohamad’s two public speeches at United Nations General Assembly (UNGA) in the years of 1999 and 2018, respectively. This account will seek to establish if there exist certain interaction achieved by stance and engagement in his UNGA speeches. In addition, this study will try to determine whether there is any change of using these rhetorical strategies in the years of 1999 and 2018. Scholars concern the changes in written discourse. For instance, Hyland and Jiang (2017) investigate the changes of academic writing and find that academic writing has become more informal in recent years. We know little of the changes in the use of rhetorical strategies in spoken discourse. The interest in Mahathir Mohamad’s speeches lies in that his speeches gain attention from scholars, such as in the field of Critical Discourse Analaysis (CDA) (David & Dumanig, 2011; Mohammed Shukry, 2013), and politics (Milne & Mauzy, 1999; Hwang, 2003). Few studies have been found in examining rhetorical resources. Speeches at UNGA have enormous global significance. Does Mahathir Mohamad construct engagement with audiences in the years of 1999 and 2018 the same way? Are there similarities and differences in the use of stance and engagement between the two speeches? This study aims to address these questions. The following section discusses the methodology in this study.